2007
DOI: 10.1039/b704568a
|View full text |Cite
|
Sign up to set email alerts
|

“Clickable” polymersomes

Abstract: Polymersomes, composed of amphiphilic polystyrene-block-poly(acrylic acid) (PS-b-PAA), with the periphery being covered with azide groups, were used for further functionalization using "click" chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
210
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(214 citation statements)
references
References 30 publications
1
210
0
3
Order By: Relevance
“…Since most polymersomes are destabilized in the presence of organic solvents, it is a prerequisite to perform this click chemistry conjugation reaction in aqueous media. Click chemistry with polymersomes in aqueous solution was introduced by van Hest and co-workers using poly(styrene)-block-poly(acrylic acid) (PS-b-PAA) diblock copolymers with terminal azide groups ( Figure 4) [32]. Different ligands, such as an alkyne bearing fluorescent dansyl probe, biotin and eGFP, have been conjugated to preformed polymersomes.…”
Section: Aminementioning
confidence: 99%
See 1 more Smart Citation
“…Since most polymersomes are destabilized in the presence of organic solvents, it is a prerequisite to perform this click chemistry conjugation reaction in aqueous media. Click chemistry with polymersomes in aqueous solution was introduced by van Hest and co-workers using poly(styrene)-block-poly(acrylic acid) (PS-b-PAA) diblock copolymers with terminal azide groups ( Figure 4) [32]. Different ligands, such as an alkyne bearing fluorescent dansyl probe, biotin and eGFP, have been conjugated to preformed polymersomes.…”
Section: Aminementioning
confidence: 99%
“…The state of the art in terms of common conjugation chemistry that fulfills all or some of these requirements is summarized in Table 1. [26,29] Horseradish peroxidase [26] and an azidofunctionalized Candida antarctica Lipase B [29] Azide Alkyne 1,4-disubstituted 1,2,3-triazole PBD-b-PEG [30,31], PS-b-PAA [32] Mannose functional polyester dendron [30,31], dansyl probe [32], biotin [32], eGFP [32] Biotin Streptavidin Biotin-Streptavidin interaction PBD-b-PEG and PEG-b-PEE [33], PMOXA-b-PDMS-b-PMOXA [17,20,34,35] Superavidin-coated microspheres [33], antibody [36], polyguanylic acid [20,34], streptavidin-modified glass surface [17], fluorescently labeled avidin [33,35] …”
Section: Conjugation To Preformed Polymersomesmentioning
confidence: 99%
“…[9][10][11] One of the great advantages of this concept was for example the possibility to combine homopolymers preliminary prepared by various living polymerization techniques, such as ringopening polymerization (ROP), ring-opening metathesis polymerization (ROMP), cationic polymerization, nitroxide-mediated radical polymerization (NMP), atom transfer radical polymerization (ATRP), and reversible addition fragmentation chain transfer polymerization (RAFT). Thus, various orthogonal and efficient coupling reactions such as thiol-ene or thiol-ene based Michael addition reactions, [12][13] and Diels-Alder reactions 14 were successfully carried out.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that six-membered ring carbonates react with amines as nucleophiles at room temperature. It is also known that copper-(I) catalysed click-reactions work at room temperature [32][33][34]. So these functional groups are perfect for connecting two building blocks without heating.…”
Section: Coupling Reaction Using the Orthogonal Coupler 3amentioning
confidence: 99%